Gestão do patrimônio arqueológico em contexto minerário: construindo um modelo a partir do ordenamento jurídico brasileiro - Morais, Filipe de (2015)
This dissertation, entitled Management of Archaeological Heritage in a Mining Context: Building a Model from the Brazilian Legal System", aims to propose a technical-scientific model for environmental licensing of potentially harmful mining activities regarding the speleological heritage in cases where it contains evidence of archaeological materials (lithics, ceramics, hearths or rock art) showing the presence of ancient indigenous occupations. Based on discussion of the theoretical, conceptual, methodological and legal bases, the text focuses on the possible interaction between the speleological comprising aspects of the physical and biotic environment, as natural environmental assets and the archaeological heritage comprising the signatures anthropogenic the past, such as cultural environmental assets. From this point of view, we propose a technical-scientific model for cultural resource management studies linked to environmental licensing of mining activities that may impact the natural cavities as natural and cultural environmental assets